2010
DOI: 10.1021/jp103645c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Potential Relief on Forming Molecular Arrays: Tryptanthrin Adsorbed on Various Si(111) Reconstructions

Abstract: To explore the effect of the substrate surface potential relief on the self-assembly of the adsorbed organic molecules, adsorption of tryptanthrin molecules on the various reconstructed Si(111) surfaces has been studied using scanning tunneling microscopy. The set of the Si(111) surface reconstructions under consideration includes atomically clean adsorbate-free Si(111)7 × 7 and metal-induced Si(111)4 × 1-In, Si(111)’5.5 × 5.5’-Cu, and Si(111)√3 × √3-Ag surfaces, each having specific surface potential relief. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Interaction of phthalocyanines with metal reconstructed Si(111) surfaces was studied earlier, and it was found that CoPc’s freely diffuse on the Si(111)-Ag-√3 × √3 R 30° surface until they form a fully ordered layer or on the passivated Si(111)-Tl-1 × 1 where CuPc forms switchable ordered domains in the presence of an aligned electric field. , The behavior of other macrocyclic molecules deposited on metal-modified silicon surfaces exhibits interesting effects such as fullerenes (C 60 ) displacing atoms from indium adlayers on Si(111) or trapping mobile vacancies on Si(111)-In-√3 × √3 . The interaction of tryptanthrin differed greatly among the clean, Cu-, In- and Ag-modified Si(111), each with a different reconstruction, which the authors attribute to differences in the surface potential relief …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of phthalocyanines with metal reconstructed Si(111) surfaces was studied earlier, and it was found that CoPc’s freely diffuse on the Si(111)-Ag-√3 × √3 R 30° surface until they form a fully ordered layer or on the passivated Si(111)-Tl-1 × 1 where CuPc forms switchable ordered domains in the presence of an aligned electric field. , The behavior of other macrocyclic molecules deposited on metal-modified silicon surfaces exhibits interesting effects such as fullerenes (C 60 ) displacing atoms from indium adlayers on Si(111) or trapping mobile vacancies on Si(111)-In-√3 × √3 . The interaction of tryptanthrin differed greatly among the clean, Cu-, In- and Ag-modified Si(111), each with a different reconstruction, which the authors attribute to differences in the surface potential relief …”
Section: Introductionmentioning
confidence: 99%
“…15 The interaction of tryptanthrin differed greatly among the clean, Cu-, In-and Ag-modified Si(111), each with a different reconstruction, which the authors attribute to differences in the surface potential relief. 16 To reduce the complexity of the Si(111)7 × 7 substrate, we use an adlayer of Sn atoms forming the well-studied Si(111)-Sn-√3 × √3R30°reconstruction (R30°descriptor omitted hereafter): 17 the isovalent Sn atoms reside in the T 4 position bonded to three nearest underlying Si atoms and are left with one unpaired electron each (i.e., dangling bond). The surface thus consists of identical Sn atoms possessing half-occupied dangling bonds.…”
Section: ■ Introductionmentioning
confidence: 99%